Limited attention, the use of accounting information and its impacts on individual investment decision making - Checon, Bianca Quirantes (2018)
As technology and capital markets complexity increases, so does the amount of accounting information disclosed by companies in their financial reports. Nowadays, we reached an impasse, where it is questionable if more information will in fact reduce information asymmetry. Previous authors strongly criticize the length of financial statements and annual reports, arguing that they should communicate more rather than just be voluminous as the current volume of information can be counterproductive to the average individual to acquire, retain and process all available information. Based on evidence of previous accounting literature on presentation format and the psychology theories of attribution theory and cognitive load theory, we hypothesize that, by manipulating accounting information using a more general accessible format such as the narrative one, individual investors are able to better understand accounting information and, thereafter, make a more effective use of it versus the concurrent non-fundamental information available in a standard investment decision making setting. To achieve our research goal, we use a mixed method research strategy with an Exploratory Sequential Design: the qualitative method act as a preparation for the quantitative one. Concerning the qualitative method, we interview- using the Q methodology approach - 31 subjects, being 13 analysts/professional investors and 18 individual investors. Our objective in this phase is to identify patterns in the usage of accounting/non-accounting information by analysts/professional investors, in contrast to individual investors\' information choices. By doing so, we can use the obtained results to base our experimental information choices regarding (a) which accounting information pieces were most preferable to professional investors and (b) the information presentation sequence to be followed in the experimental setting. Next, we develop a 2 X 2 between-subjects experimental design in which we manipulate the presentation format of a hypothetical company between the traditional \'tabular and footnotes\' design versus the narrative content-only design. We also vary the financial performance between \'good\' and \'bad\' to check if the variables of interest would impact (a) investment propensity on the company\'s shares and (b) the amount of information retrieved from memory. As our main results, we find that the narrative format per se does not impact investment propensity and that the alternative presentation format is beneficial for participants with less than 5 years of investment experience in capital markets in the poor financial performance condition, adjusting their investment propensity to the same investment propensity level of more experienced investors.